2022
DOI: 10.1093/bjs/znac269.318
|View full text |Cite
|
Sign up to set email alerts
|

984 The Efficacy of Different Nerve Transfers to Restore Elbow Flexion in Adults Following Brachial Plexus Injury: A Systematic Review and Meta-Analysis

Abstract: Aim There are numerous donors available for neurotisation of the musculocutaneous nerve, following traumatic brachial plexus injury (BPI). However, there is uncertainty over which method is most effective for restoring elbow flexion. We set out to summarise and compared different nerve transfers for restoring elbow flexion after traumatic BPI in adults. Method Medline, Embase, medRxiv and bioRxiv were systematically searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recent work has shown that the time from injury to reconstruction in adults with BPI is linearly associated with functional outcomes, whereby each month of delay to neurotisation reduces the odds of meaningful recovery by 7% 31 . Moreover, the choice of donor nerve(s) used for reconstruction directly in uences the chance of useful recovery 31 . This observation cannot be completely explained by local anatomical factors (such as donor-recipient axon counts) and we speculate that the plastic potential of the cortex for some donor nerves may be greater than others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that the time from injury to reconstruction in adults with BPI is linearly associated with functional outcomes, whereby each month of delay to neurotisation reduces the odds of meaningful recovery by 7% 31 . Moreover, the choice of donor nerve(s) used for reconstruction directly in uences the chance of useful recovery 31 . This observation cannot be completely explained by local anatomical factors (such as donor-recipient axon counts) and we speculate that the plastic potential of the cortex for some donor nerves may be greater than others.…”
Section: Discussionmentioning
confidence: 99%
“…In both animals 29,30 and humans 31 early nerve repair after BPI yields better outcomes. Recent work has shown that the time from injury to reconstruction in adults with BPI is linearly associated with functional outcomes, whereby each month of delay to neurotisation reduces the odds of meaningful recovery by 7% 31 . Moreover, the choice of donor nerve(s) used for reconstruction directly in uences the chance of useful recovery 31 .…”
Section: Discussionmentioning
confidence: 99%
“…injury, particularly if we do not have visibility proximal to the foramina (Bourke et al, 2021;Jivan et al, 2009;Wade et al, 2018aWade et al, , 2018bWade et al, , 2019. Specifically in adults with traumatic brachial plexus injuries, each month of delay from the time of injury to reconstruction reduces the probability of achieving M4 elbow flexion by 7% (Vernon Lee et al, 2023) Given that early reconstruction is associated with more favourable outcomes, medical tests for diagnosing nerve injury should be accurate enough to differentiate those who need early intervention from those who may recover spontaneously.…”
Section: Trauma/injury: Diagnosis and Monitoringmentioning
confidence: 99%